Unified system of public authority: debatable aspects of legal regulation - O. A. Kozhevnikov; A. N. Kostyukov; A. A. Larichev (Правоприменение)
The subject of this study is the legal regulation of the unified system of public authority in the Russian Federation. Its purpose is to determine the theoretical approaches and practice of legislative regulation of a unified system of public authority, which is unfolding after the adoption of amendments to the text of the Constitution of the Russian Federation in 2020. The main hypothesis, which authors propose is that there is a contradiction between the norms of the acts, governing organization and activities of public authorities, and those norms in their relationship with the constitutional norms governing the relevant relations. In the course of the work, the authors used both general research methods, including methods of analysis and synthesis, as well as field-specific ones, including the formal legal method. The authors believe that the difficulties in reflecting public authority in normative regulation lie primarily in the fact that neither in Soviet legal research, nor in the current Russian legal thought, issues of public authority have been considered meaningfully and in detail. Its content and structure do not have a clear, complete doctrinal understanding. Foreign experience, however, shows that such a clear understanding at the theoretical level is absent in foreign jurisdictions either.